Partial substitution of chemical fertilizers with maize straw: Seeking long‐term improvement of rice yield by raising quality indicators of a red paddy soil. (3rd August 2022) - Zhang, Lian; Hou, Kun; Zhang, Qiong; He, Shifu; Long, Guangli; Yin, Lichu; Zhu, Hongmei; Tian, Chang; Luo, Gongwen; Rong, Xiangmin; Han, Yongliang
Abstract: Straw application increases crop yield, but the underlying mechanisms of straw‐substitution for chemical fertilizer on yield is not completely understood. We hypothesized that straw application improves crop yield by improving soil quality. In order to clarify how partial substitution of chemical fertilizers with maize straw affects soil properties and the specific contribution of soil properties to double‐cropping rice yield, we selected a long‐term positioning test station operated since 1982 and designed three fertilization treatments: (1) single chemical fertilizers (CF); (2) medium replacement by maize straw under which 1/3 of nitrogen (N) fertilizer was replaced (MS); and (3) high replacement by maize straw under which 2/3 of N fertilizer was replaced (HS). The yield under HS of late and early rice increased by 42.66% and 25.04% in 2019 and 2020, respectively. Long‐term straw application significantly decreased soil bulk density, increased total porosity, and improved the stable aggregates content (>0.25 mm). Straw application increased soil urease, protease, alkaline phosphatase (ALP), acid phosphatase (ACP) and catalase activities, microbial biomass carbon (C), microbial biomass N, and nutrients compared with CF. The structural equation model indicated that the tested soil properties explained 77% of the variations in observed rice yield. The rice yield was mainly indirectly affected by soil organic matter (SOM), microbial biomass, and enzyme activities. The results showed that straw substituted for chemical fertilizers increased rice yield. The key factors affecting yield under long‐term fertilization were SOM, microbial biomass, and enzyme activity, rather than soil N, phosphorus (P) nutrient contents, and bulk density.